Evaluation of Disaster Medicine Preparedness among Healthcare Profession Students: A Cross-Sectional Study in Pakistan - Ali Hassan Gillani (20280366) (2020)
Background: Disasters are devastating incidents, especially when occurring suddenly and causing damage, great loss of life, or suffering. Disasters can affect health and the social and economic development of a nation. The article analyzes the knowledge (K), attitude (A), and readiness to practice (rP) of healthcare professional students in universities in Pakistan. Methods: We carried out a cross-sectional study using a pretested and validated self-administered disaster medicine and preparedness questionnaire. The study recruited 310 students. Responses were scored and categorized as high (75th quartile), moderate (75–25th quartiles), and low (25th quartile). Independent t-test, one-way ANOVA, Pearson correlation, and regression analyses were performed at an alpha level of 0.05. Results: The study found that most of the students had moderate knowledge, attitude, readiness to practice, and total KArP scores. All K, A, and rP scores were significantly correlated with overall KArP scores. Knowledge and attitude factors were significant predictors of readiness to practice. Conclusions: We strongly believe that educators and health policymakers should build a strong curriculum in disaster medicine management and preparedness to prepare competent future healthcare professionals for the nation. Other Information Published in: International Journal of Environmental Research and Public Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijerph17062027